Enhancing Supportive Leadership, Affective Organizational Commitment and Work Engagement through ODI : A Case Study of Gold Power Company Limited, Myanmar - Tin, Thida; Wisankosol, Papitchaya (ABAC ODI JOURNAL Vision. Action. Outcome, 2022)
This participatory action research aims to enhance work engagement and affective commitment by designing and delivering the necessary organizational development interventions (ODIs) at the focal company, the Gold Power Company Limited (GPCL). The researcher employed action research method to answer three objectives, comprising 1) Diagnosing the current situations of supportive leadership, affective organizational commitment, and work engagement at Gold Power Company, 2) Designing and experimenting with the ODIs of supportive leadership, affective organizational commitment, and work engagement, and 3) Measuring the effects of ODIs on supportive leadership, affective organizational commitment, and work engagement. The research site is at Gold Power Company, Myanmar, involving the managers (n=50) who are full-time employees. This study employs quantitative survey research method with the use of structured questionnaire with 5-point Likert scale as research instruments, where the instruments are validated and tested with Cronbach Alpha Co-Efficient. The results indicate that the ODIs have improved supportive leadership (P=0.000), Affective organizational commitment (P=0.000), and work engagement (P=0.000). The recommendations include 1) providing more leadership training to enhance supportive leadership and people-oriented leadership behaviors, 2) encouraging middle managers to use more of supportive leadership behaviors, 3) suggesting HR department at GPCL to inspect affective organizational commitment and work engagement level routinely, and to include leader’s supportive behaviors as KPIs in performance appraisal.